2013
DOI: 10.1093/ejo/cjt068
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal airway dimensions: a cephalometric, growth-study-based analysis of physiological variations in children aged 6-17

Abstract: The high interindividual variations of 'p' and 't' render the use of reference values problematic. Contrary to other craniofacial structures, neither age-related changes nor sexual dimorphism were found for 'p' and 't'. Any associations to antero-posterior cephalometric characteristics seem low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 29 publications
(46 reference statements)
6
28
0
3
Order By: Relevance
“…The similar finding was also reported by other lateral cephalometric analysis or 3-dimentional CT research [34,35]. In addition, Taylor et al [36] reported that the growth of the oropharynx has two periods of accelerated change (6-9 years and 12-15 years) and two periods of quiescence (9-12 years and 15-18 years) for the growth of oropharynx, but Mislik et al [37] found there was no radical change in the retropalatal and retroglossal oropharynx from 6 to 17 years of age, and considered that the upper airway dimensions were formed and matured during the early periods of growth. Because the chronological regularity of growth of Chinese children is still unclear, we consider that the norms obtained from 12-year-old Chinese children are only relevant to the age around 12-year-old.…”
Section: Discussionsupporting
confidence: 81%
“…The similar finding was also reported by other lateral cephalometric analysis or 3-dimentional CT research [34,35]. In addition, Taylor et al [36] reported that the growth of the oropharynx has two periods of accelerated change (6-9 years and 12-15 years) and two periods of quiescence (9-12 years and 15-18 years) for the growth of oropharynx, but Mislik et al [37] found there was no radical change in the retropalatal and retroglossal oropharynx from 6 to 17 years of age, and considered that the upper airway dimensions were formed and matured during the early periods of growth. Because the chronological regularity of growth of Chinese children is still unclear, we consider that the norms obtained from 12-year-old Chinese children are only relevant to the age around 12-year-old.…”
Section: Discussionsupporting
confidence: 81%
“…Számítógépes kefalometriás kiértékeléshez a zürichi Craniofacialis Növekedés Tanulmánya során meghatározott pontokat, paramétereket és átlagértékeket használtuk fel, azon egyszerű oknál fogva, hogy az említett tanulmány európai alanyok értékeit veszi figyelembe, és azok minden bizonnyal közelebb állnak az általunk tanulmányozott alanyok értékeihez [16].…”
Section: Megbeszélésunclassified
“…Morfologiczne korelacje struktur kostnych twarzoczaszki i szyjnego odcinka kręgosłupa z górnymi drogami oddechowymi (GDO) od lat stanowią temat badań naukowych. W piśmiennictwie odnaleźć możemy badania pokazujące istnienie zależności pomiędzy wymiarami GDO a morfologią tkanek twardych twarzoczaszki [1][2][3] oraz badania pokazujące zmiany zachodzące w wymiarach GDO pod wpływem leczenia ortodontycznego. 4,5 Istnienie korelacji między morfologią GDO a wiekiem osób badanych potwierdzają liczne badania.…”
Section: Wstępunclassified
“…Morphological correlations of craniofacial and cervical spine bone structures with the upper respiratory tract (URT) have been the focus of scientific studies for many years now. The literature points to some studies illustrating relations between the URT dimensions and morphology of the craniofacial hard tissues, [1][2][3] as well as investigations showing changes in URT dimensions resulting from orthodontic procedures. 4,5 The correlation between URT morphology and age of the evaluated individuals has been confirmed by numerous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation